2013
DOI: 10.1177/0040517513478460
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide application in the textile industry: surface tailoring and water barrier attributes as parameters with direct implication in comfort performance

Abstract: The present study focuses on surface tailoring and water barrier attributes of zinc oxide (ZnO)-polyester composite textile materials. The surface properties, such as surface topography and roughness, composite compositions as well as thermal stability of ZnO-100% polyester textile composite materials treated through a padding process with different concentrations of ZnO dispersions as active agent in water and methanol were studied. The results show that 3% ZnOtextile composite material have enhanced water ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Whereas the thermal stability of cellulose fibers was not improved by ZnO, the amount of char residue was significantly increased [13,96,142]. In contrast, the thermal stability of ZnO-treated polyester fibers even decreased compared to untreated fibers [143]. However, the loading of ZnO onto an organic-inorganic hybrid soloxane polymer film significantly modified a decomposition pathway of the coating, which significantly enhanced the thermal stability of the polyester fibers [106].…”
Section: Flame Retardancymentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the thermal stability of cellulose fibers was not improved by ZnO, the amount of char residue was significantly increased [13,96,142]. In contrast, the thermal stability of ZnO-treated polyester fibers even decreased compared to untreated fibers [143]. However, the loading of ZnO onto an organic-inorganic hybrid soloxane polymer film significantly modified a decomposition pathway of the coating, which significantly enhanced the thermal stability of the polyester fibers [106].…”
Section: Flame Retardancymentioning
confidence: 99%
“…There are only a few papers involving ZnO-based flame-retardant textiles. In these studies, ZnO alone or in combination with organic phosphorus compounds was applied to cotton, polyester or cotton/polyester blends [7,84,[142][143][144], but for technical applications, jute and sisal fibers were also used as textile substrates [6,96]. The results showed that the flame retardancy of ZnO-coated cellulose fibers was significantly enhanced if bulk ZnO was replaced with ZnO NPs [6].…”
Section: Flame Retardancymentioning
confidence: 99%
“…Through a comparison of different concentrations (1%, 3%, 5% and 7%) of ZnO dispersions either in water or methanol to make the surface of ZnO-polyester composite textile materials, Rimbu et al . 26 demonstrated that the larger concentration leads to agglomerations and a diminished coating quality. In order to mitigate the problem of aggregation, the process of sonication can be used.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is an efficient antimicrobial agent for a broad range of bacteria targets. It can effectively kill Gram positive and Gram negative bacteria at an appropriate dosage [ 33 , 34 ]. As shown in Fig 8 , there was a similar zone of inhibition against S .…”
Section: Resultsmentioning
confidence: 99%